2014
DOI: 10.1111/bcp.12449
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and relative risk of grade 3 and 4 diarrhoea in patients treated with capecitabine or 5‐fluorouracil: a meta‐analysis of published trials

Abstract: AIMCapecitabine is an oral fluoropyrimidine that can effectively replace infusional 5-fluorouracil (5-FU) for treatment of colorectal, gastric and breast cancer. This study aims to analyze the incidence and the relative risk of grade 3 and 4 diarrhoea in patients treated with capecitabine or 5-FU in randomized clinical trials (RCTs). METHODSMEDLINE and Cochrane Library were reviewed for RCTs that compared capecitabine with 5-FU for treatment of solid malignancies. The incidence and relative risk (RR) of grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
(59 reference statements)
0
24
1
1
Order By: Relevance
“…The diarrhea usually starts at the end of the second or in the third week, is mostly mild, recovers after a few days with sometimes a necessity of treatment with anti-motility agents such as loperamide. Grade 3–4 diarrhea occurs in 11.4% of patients treated with capecitabine monotherapy [ 1 ]. In contrast, in patients with a DPD deficiency the diarrhea starts often within the first week and is life threatening [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diarrhea usually starts at the end of the second or in the third week, is mostly mild, recovers after a few days with sometimes a necessity of treatment with anti-motility agents such as loperamide. Grade 3–4 diarrhea occurs in 11.4% of patients treated with capecitabine monotherapy [ 1 ]. In contrast, in patients with a DPD deficiency the diarrhea starts often within the first week and is life threatening [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin can also cause diarrhea but typically starts early after administration within 3–4 days and resolves after 1–2 days without any intervention. In patients treated with the combination of capecitabine and oxaliplatin, grade 3–4 diarrhea occurs in approximately 18% of cases [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mechanisms involved in the transcellular transport of FTD in the intestines were investigated using ENTexpressing Xenopus oocytes and HIEC monolayers in order to clarify its relationships with: (1) the sufficient membrane permeability of FTD to achieve relatively high absorption (~60%) in humans (Lee et al, 2016) despite its hydrophilic characteristics (log P = −0.452, pH 7), and (2) the lower incidence of intestinal toxicity of FTD (3%) (Mayer et al, 2015) in patients administered TAS-102 than in those given other chemotherapeutic agents such as capecitabine (17.0%), 5-FU (12.9%) and irinotecan (15%) (Iacovelli et al, 2014;Negoro et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials revealed that the frequency of severe diarrhea caused by TAS‐102 (diarrhea of grade 3 or higher in 3% of the 533 patients who received TAS‐102 (Mayer et al, ) was lower than that by other chemotherapeutic agents such as capecitabine (17.0%), 5‐fluorouracil (12.9%) and irinotecan (15%) (Iacovelli et al, ; Negoro et al, ). These findings indicate that ENTs play a significant role in the basolateral efflux of FTD, which ameliorates the gastrointestinal toxicity of FTD by reducing the intracellular accumulation of FTD in the intestines.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea occurring during AC may be due to side effects of chemotherapy or it may be a symptom of dumping syndrome shortly after surgery [ 16 17 ]. It is important to know whether diarrhea persists after stopping the chemotherapy or after eating a large quantity of food or carbohydrates.…”
Section: Discussionmentioning
confidence: 99%